The Effect of Economic Growth and Taxes on Investment in Indonesia - Tsania Mir Atunnisa'; Arfian Rudi Candra; Grace Eguine Malau; Ema Nanda Hidayah; Jovita Nuril Aprilya; Febriadi Akbar Satrio; Zainul Anam (Jurusan Ilmu Ekonomi Fakultas Ekonomi Universitas Trunojoyo Madura, 2026)
This study aims to analyze the impact of economic growth and Taxation on Investment in Indonesia from 2015 to 2024. The research method employed is a quantitative approach, utilizing panel data regression analysis with the Fixed Effects Model (FEM) across 37 provinces in Indonesia. The results show that simultaneously, economic growth and taxes have a significant effect on Investment. Economic growth has a partially positive and significant effect on Investment, while taxes exhibit a positive but insignificant effect. The coefficient of determination (R²) value of 73.34% indicates that most of the variation in Investment can be explained by these two variables. At the same time, the rest is influenced by other factors outside the model, such as interest rates and other fiscal policies. The results of this study underscore the importance of stable economic policies, an efficient tax system, and effective tax revenue management in promoting a favorable investment climate and sustainable economic growth in Indonesia. These findings are expected to be taken into consideration by the government in formulating more effective fiscal policies to strengthen national economic competitiveness. Keywords: Economic Growth, Tax, Investment, Panel Data, Fixed Effect Model